Peran Brand Image dan Social Media Marketing dalam Repeat Purchase Pada Media What’s New Bali - Felix Tonda; Teguh Hadisukarno; Putu Surya Laksana Rahjasa (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2024)
This study examines how brand image and social media marketing influence repeat purchases on What's New Bali media. The study uses a qualitative research method. The number of respondents used in this study were 5 respondents from 5 five-star hotels in ITDC who had made repeat purchases on What's New Bali media twice or more. The data collection procedure in this study used interview guidelines. The results obtained in this study prove that there is an influence of brand image and social media marketing on repeat purchases. With the need for a marketer to expand hotel awareness and implement hotel marketing strategies in social media, it can influence repeat purchases on What's New Bali media.